Pengaruh Latihan Aerobik Terhadap Jumlah Trombosit pada Mahasiswa Program Studi Keperawatan Batu RajaTahun 2012 - Suparno Suparno (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2012)
Background: Platelets are fragments or fragments of megakaryocyte cytoplasm not cored from a size 1-4 microns and circulate in the blood circulation for 10 days. Platelets play an important role in the formation of blood clots. Physical exercises are conducted regularly to improve one’s health. Aerobic exercise is considered beneficial, but the sport is sometimes causing sudden cardiac death. The study of the mechanism of the effect of aerobic exercise on arterial thrombosis is very important, not only for the prevention of cardiovascular events but also for sporting activities are safe for health. The purpose of this study was to see the effect of aerobic exercise on platelet counts in the Student Nursing Program Balfour. Methods: The design used in this study are no comparative clinical trials, have been conducted in the laboratory of Ibn Soetowo Hospital Nursing Prodii Balfour and Balfour. Subjects numbered 36 respondents randomly. Training program conducted a walk for 30 minutes (DNM 70-85%) for 4 weeks with a frequency of three times a week. Analysis by paired t-test . Results: There was an increase in platelet count after exercise, but not statistically significant (p = 0.276). Conclusion: There is no effect of aerobic exercise on platelet counts in Mahasiswa Program Studi Keperawatan Baturaja tahun 2012.